Characteristics and risk factors for invasive fungal infection in hospitalized patients with acute-on-chronic hepatitis B liver failure: a retrospective cohort study from 2010 to 2023 - Wu, Yin-Ping; Li, Feng-Cai; Ma, Hang-Yu; Yang, Xue-Yan; Zuo, Jing; Tian, Yu-Xin; Lv, Li; Wang, Kai; Fan, Yu-Chen (Frontiers in Microbiology, 2024)
Background and aim: The global burden of invasive fungal infections (IFIs) is emerging in immunologic deficiency status from various disease. Patients with acute-on-chronic hepatitis B liver failure (ACHBLF) are prone to IFI and their conditions are commonly exacerbated by IFI. However, little is known about the characteristics and risk factors for IFI in hospitalized ACHBLF patients. Methods: A total of 243 hospitalized ACHBLF patients were retrospectively enrolled from January 2010 to July 2023. We performed restricted cubic spline analysis to determine the nonlinear associations between independent variables and IFI. The risk factors for IFI were identified using logistic regression and the extreme gradient boosting (XGBoost) algorithm. The effect values of the risk factors were determined by the SHapley Additive exPlanations (SHAP) method. Results: There were 24 ACHBLF patients (9.84%) who developed IFI on average 17.5 (13.50, 23.00) days after admission. The serum creatinine level showed a nonlinear association with the possibility of IFI. Multiple logistic regression revealed that length of hospitalization (OR=1.05, 95% CI: 1.02-1.08, P=0.002) and neutrophilic granulocyte percentage (OR=1.04, 95% CI: 1.00-1.09, P=0.042) were independent risk factors for IFI. The XGBoost algorithm showed that the use of antibiotics (SHAP value=0.446), length of hospitalization (SHAP value =0.406) and log(qHBV DNA) (SHAP value=0.206) were the top three independent risk factors for IFI. Furthermore, interaction analysis revealed no multiplicative effects between the use of antibiotics and the use of glucocorticoids (P=0.990). Conclusion: IFI is a rare complication that leads to high mortality in hospitalized ACHBLF patients, and a high neutrophilic granulocyte percentage and length of hospitalization are independent risk factors for the occurrence of IFI.